2010
DOI: 10.1371/journal.pone.0012059
|View full text |Cite
|
Sign up to set email alerts
|

Different Oxidative Stress Response in Keratinocytes and Fibroblasts of Reconstructed Skin Exposed to Non Extreme Daily-Ultraviolet Radiation

Abstract: Experiments characterizing the biological effects of sun exposure have usually involved solar simulators. However, they addressed the worst case scenario i.e. zenithal sun, rarely found in common outdoor activities. A non-extreme ultraviolet radiation (UV) spectrum referred as “daily UV radiation” (DUVR) with a higher UVA (320–400 nm) to UVB (280–320 nm) irradiance ratio has therefore been defined. In this study, the biological impact of an acute exposure to low physiological doses of DUVR (corresponding to 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
81
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(90 citation statements)
references
References 45 publications
(56 reference statements)
7
81
0
2
Order By: Relevance
“…Derrico et al, 2007 reported that keratinocytes were more resistant than fibroblasts to the lethal effects of UVR and more efficient in the removal of cyclobutane pyrimidine dimers (D'Errico et al, 2007). Marionnet et al, 2010 found that there was a greater oxidative response in dermal fibroblasts in comparison to keratinocytes (demonstrated by a more rapid induction of related gene expression in these cells when irradiated with a solar simulator producing UVR approximating daily, non-zenithal sunlight, proportionally richer in UVA wavelengths (Marionnet et al, 2010). Bernerd and Asselineau, 1998 have also suggested differential cell type sensitivity to UVA supporting the opinion that dermal fibroblasts are less resistant to UVA in experiments that exposed skin equivalents to 30 J/cm 2 UVA1 (Bernerd and Asselineau, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Derrico et al, 2007 reported that keratinocytes were more resistant than fibroblasts to the lethal effects of UVR and more efficient in the removal of cyclobutane pyrimidine dimers (D'Errico et al, 2007). Marionnet et al, 2010 found that there was a greater oxidative response in dermal fibroblasts in comparison to keratinocytes (demonstrated by a more rapid induction of related gene expression in these cells when irradiated with a solar simulator producing UVR approximating daily, non-zenithal sunlight, proportionally richer in UVA wavelengths (Marionnet et al, 2010). Bernerd and Asselineau, 1998 have also suggested differential cell type sensitivity to UVA supporting the opinion that dermal fibroblasts are less resistant to UVA in experiments that exposed skin equivalents to 30 J/cm 2 UVA1 (Bernerd and Asselineau, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…58,59 Interestingly, the rate of CPD removal in the HSE-DED was comparable not only to studies using other organotypic skin constructs, but also to the in vivo experiments mentioned earlier. 49,60 This indicates that the cells in the HSE-DED retain the ability to initiate DNA damage response and repair pathways, which potentially enables the screening of novel mechanisms to enhance these processes.…”
Section: Discussionmentioning
confidence: 99%
“…Modulated genes were related to oxidative stress (see [4]), transcription and signaling, heat shock proteins, cytokines, extracellular matrix (ECM, especially in fibroblasts) and epidermal differentiation (specifically in keratinocytes). A particular attention was paid to the expression of ECM and epidermal differentiation genes ( Fig.…”
Section: Journal Of Dermatological Sciencementioning
confidence: 99%
“…The experimentations included 4 independent samples for each time point at each type of exposure. Epidermis and dermis of reconstructed skin were separated using fine forceps [4]. After RNA extraction from each cell type (Rneasy midi-kit, Qiagen) and DNAse I treatment, the same amount of total RNA obtained from the 4 samples in the same conditions were pooled and used for hybridization on cDNA arrays (nylon membrane spotted with cDNAs using a Piezzoarray (PerkinElmer)).…”
mentioning
confidence: 99%